Jurists and jurisprudence in medieval Italy: texts and contexts - Cavallar, Osvaldo (Toronto studies in medieval law, 2020)
"Jurists and Jurisprudence in Medieval Italy is an original collection of texts exemplifying medieval Italian jurisprudence, known as the ius commune. Translated for the first time into English, many of the texts exist only in early printed editions and manuscripts. Featuring commentaries by leading medieval civil law jurists, notably Azo Portius, Accursius, Albertus Gandinus, Bartolus of Sassoferrato, and Baldus de Ubaldis, this book covers a wide range of topics, including how to teach and study law, the production of legal texts, the ethical norms guiding practitioners, civil and criminal procedures, and family matters. The translations, together with context-setting introductions, highlight fundamental legal concepts and practices and the milieu in which jurists operated. They offer entry points for exploring perennial subjects, such as the professionalization of lawyers, the tangled relationship between law and morality, the role of gender in the socio-legal order, and the extent to which the ius commune can be considered an autonomous system of law."--